Перспективные полупроводниковые материалы для использования в силовой электронике - Критская, Татьяна Владимировна; Быткин, Сергей Витальевич (НТУ "ХПИ", 2018)
Технологии высокотемпературных и радиационно-стойких силовых полупроводниковых приборов (СПП) используют структуры на основе SiC, GaN. Мировой рынок дискретных силовых приборов в 2024 г. предположительно составит ~ $23 млрд., доля приборов на основе кремния ≅87%. Предложены методы специального легирования монокристаллов CZ-Si и обработки, повышающей механические свойства Si, а также радиационную и термическую стабильность СПП на основе CZ-Si.

The world market of discrete power devices in 2024 will be ~ $ 23 billion, the share of devices based on silicon will be ~ 87%, due to the price availability and the mastery of silicon technologies. The inflow of investments, the success in mastering SiC, GaN, diamond, heterostructure technologies, and the pressing need for the manufacture of new high-temperature, radiation-resistant power semiconductor devices (PSs) with better performance and frequency characteristics, in comparison with silicon devices, contribute to the growing popularity of these materials from manufacturers of devices. The pressure of legislative and commercial requirements related to energy efficiency and cost reduction contributes to the successful development of a new element base using these materials for the fifth generation (5G) communication networks, broadband Internet access systems, satellite systems, microwave transmitters, civil and military radar stations, for energy and transport. However, the possibilities of silicon in terms of increasing thermostability, radiation resistance, reliability of PSs and industrial development are far from exhaustion. Methods for the special alloying of CZ-Si single crystals and for processing, improving the mechanical properties of single crystals, as well as evidence of an increase in the radiation and thermal stability of silicon-based PSs are proposed.
Perspective semiconductor materials for the using in the power electronics
Keywords: силовой полупроводниковый прибор; гетероэпитаксия; кремний; монокристалл; легирование; термостабильность; радиационная стойкость; power device; heterostructure; single crystal; doping